HYBRID ENGLISH LEARNING FOR NON-ENGLISH DEPARTMENT STUDENTS: UNVEILING THE CHALLENGES AND PROBLEMS - Fran Lina, Marisa; Suriyah, Eni (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2024)
Hybrid learning in this research is a combination of WhatsApp Group online learning with restricted face-to-face learning. This facilitates the learning needs of students who have been accustomed to being online for more than two semesters. This study focuses on (1) how are the perspectives of non-English Department students towards hybrid English learning? (2) what are the challenges and problems they experienced during hybrid English learning? Data from the Google Form for English courses were analyzed qualitatively with a descriptive approach and student interviews were also analyzed qualitatively with thematic analysis. The results show that, first, students have better understanding in hybrid class than online class and they also feel challenged to answer quizzes and questions in an online and offline group of hybrid class; second, low English skill students are easier to understand in hybrid learning, the weather and time management challenge becomes new issues from this research. They affect students' readiness problems of hybrid learning who come late to the offline class. This study also offers English lecturers by making students disciplined in attending hybrid classes and activating their learning enthusiasm and speed of language response.